2010
DOI: 10.1109/tmag.2010.2043719
|View full text |Cite
|
Sign up to set email alerts
|

Robust Optimization Utilizing the Second-Order Design Sensitivity Information

Abstract: This paper presents an effective methodology for robust optimization of electromagnetic devices. To achieve the goal, the method improves the robustness of the minimum of the objective function chosen as a design solution by minimizing the second-order sensitivity information, called a gradient index (GI) and defined by a function of gradients of performance functions with respect to uncertain variables. The constraint feasibility is also enhanced by adding a GI corresponding to the constraint value. The disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…Starting with an initial design, the deterministic and RBDO optima are presented in Table 1. The result of RDO in the previous article [2], where the gradients of performance function required for the second-order sensitivity information were exploited, is added in Table 1 for proving the validity of RBDO. It is observed that total number of function calls of RBDO is more than four times as high as that of DO because of the inherent double-loop optimization structure.…”
Section: Comparison Of Different Smes Designsmentioning
confidence: 99%
See 3 more Smart Citations
“…Starting with an initial design, the deterministic and RBDO optima are presented in Table 1. The result of RDO in the previous article [2], where the gradients of performance function required for the second-order sensitivity information were exploited, is added in Table 1 for proving the validity of RBDO. It is observed that total number of function calls of RBDO is more than four times as high as that of DO because of the inherent double-loop optimization structure.…”
Section: Comparison Of Different Smes Designsmentioning
confidence: 99%
“…[1][2][3][4][5][6]. The methodology for treating optimization problems in the presence of uncertainties of design parameters/variables can be categorized into two approaches.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of robust optimization methods have been proposed to be applied to electromagnetic devices [2][3][4][5][6]. A large part of the optimization approaches use the gradient index (GI) of parameters to represent the robustness due to its simplicity and low computational cost [7].…”
Section: Introductionmentioning
confidence: 99%